Improving Medical Education in Oncology: Enhancing Students’ Understanding of Cancer Treatments Through Multidisciplinary Clinical Rotations - Arnaud Beddok; Leila Bouazzi; Coralie Barbe; Pierre Martin; Julian Gratiaux; Philippe Guilbert; Louis Job; Amélie Lemoine; David Morland; Dimitri Papathanassiou; Stéphane Perin; Yacine Merrouche; et al. (Journal of Cancer Education, 2025)

Correction: Research strategies to catalyze agroecological transitions in low- and middle-income countries - Sarah K. Jones; Nadia Bergamini; Francesca Beggi; Didier Lesueur; Barbara Vinceti; Arwen Bailey; Fabrice A. DeClerck; Natalia Estrada-Carmona; Carlo Fadda; Etienne M. Hainzelin; Danny Hunter; Chris Kettle; et al. (Sustainability Science, 2022)

Research strategies to catalyze agroecological transitions in low- and middle-income countries - Sarah K. Jones; Nadia Bergamini; Francesca Beggi; Didier Lesueur; Barbara Vinceti; Arwen Bailey; Fabrice A. DeClerck; Natalia Estrada-Carmona; Carlo Fadda; Etienne M. Hainzelin; Danny Hunter; Chris Kettle; et al. (Sustainability Science, 2022)
Governments are updating national strategies to meet global goals on biodiversity, climate change and food systems proposed in the Convention on Biological Diversity post-2020 framework and agreed at the United Nation’s Climate Change Conference (COP26) and Food Systems Summit (UNFSS). This represents a unique and crucial opportunity to integrate and accelerate food system actions to tackle interconnected global challenges. In this context, agroecology is a game-changing approach that can provide the world’s growing population with nutritious, healthy affordable food, ensure fair incomes to farmers and halt and reverse the degradation of the natural environment. Here, we explore agroecological transition pathways in four case studies from low- and middle- income countries and identify catalysts for change. We find that enabling policy and market environments, participatory action research and local socio-technical support each plays a critical role in stimulating transitions towards agroecology. We propose strategies and priorities for research to better support agroecological transitions using these catalysts of change as entry points. Engagement of governments, private sector, civil society, farmers and farm workers in this research agenda is essential.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)